Greening world trade: The Malaysian perspective on emerging issues and policy responses - Devadason, E.S.; Chenayah, S. (2011)
The rising environmental trade barriers (ETBs), emanating largely from developed countries has affected the export interests of developing economies. Much contention remains that ETBs are a merely a guise for protectionism instead of reflecting green concerns as the associated costs for compliance can be prohibitive for developing countries. For a small but trade-dependent economy like Malaysia, environmental measures such as product standards and eco-labeling pose threats in terms of market access and industrial competitiveness. This paper addresses the emerging ETBs that have a direct bearing on Malaysia's exports and the policy actions taken in responding to the environmental challenge.